The Importance of Reading and Writing Literacy in Holistic Curriculum Development in Elementary Schools - Cahyani, Ni Luh Putu Risna; Dewi, Ni Ketut Trianti; Suarini, Ni Ketut Yunita; Dwiadiningsih, Ni Kadek Putri Ayu; Apriliani, Ni Luh Gede Witri; Werang, Basilius Redan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research uses a qualitative descriptive approach to understand the condition of students' reading and writing literacy at SD Negeri 3 Kalianget and the impact of the interventions carried out. Reading and writing literacy is becoming increasingly vital in the era of globalization and digitalization. This research evaluates the effectiveness of interventions at SD Negeri 3 Kalianget to improve student literacy. By empowering libraries and open spaces, this effort aims to increase students' interest in reading, literacy skills and learning behavior. Data from observations, interviews and documentation were analyzed qualitatively. Challenges such as resources and teacher training were also identified. It is hoped that consistent support and implementation will improve students' literacy holistically, preparing them for a complex future.